2010
DOI: 10.1186/cc9393
|View full text |Cite
|
Sign up to set email alerts
|

High serum cortisol level is associated with increased risk of delirium after coronary artery bypass graft surgery: a prospective cohort study

Abstract: IntroductionThe pathophysiology of postoperative delirium remains poorly understood. The purpose of this study was to examine the relationship between serum cortisol level and occurrence of early postoperative delirium in patients undergoing coronary artery bypass graft (CABG) surgery.MethodsA total of 243 patients undergoing elective CABG surgery were enrolled. Patients were examined twice daily during the first five postoperative days and postoperative delirium was diagnosed by using the Confusion Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
107
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(130 citation statements)
references
References 62 publications
7
107
1
8
Order By: Relevance
“…Like other researchers, 10,11 we found that patients with postoperative delirium generally were older and had more comorbid conditions than did patients without delirium. Additionally, certain factors associated with cardiac surgery procedures and outcomes were also associated with the development of postoperative delirium, including length of surgery time and time on cardiopulmonary bypass.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Like other researchers, 10,11 we found that patients with postoperative delirium generally were older and had more comorbid conditions than did patients without delirium. Additionally, certain factors associated with cardiac surgery procedures and outcomes were also associated with the development of postoperative delirium, including length of surgery time and time on cardiopulmonary bypass.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies 11,17 also indicated that patients with postoperative delirium have longer hospital stays. Additionally, because of the increased likelihood of impaired functionality in patients with postoperative delirium, patients with this complication are more likely than patients without delirium to be discharged to a skilled nursing facility, or, if discharged home, are more likely to need home health assistance.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…21,22 Twice daily (in the morning from 0800 h to 1000 h and in the evening from 1800 h to 2000 h) until the seventh day after surgery, we assessed delirium by the Confusion Assessment Method for the ICU (CAM-ICU); (appendix), 23 which has been validated in Chinese patients in the ICU setting 24 and the feasibility of which had been established in our other studies. 25,26 CAM-ICU addresses the four features of delirium, namely, acute onset of mental status changes or a fl uctuating course, inattention, disorganised thinking, and altered level of consciousness. To achieve the diagnosis of delirium, a patient had to display acute onset of mental status changes or fl uctuating course and inattention, with either disorganised thinking or altered level of consciousness.…”
Section: Discussionmentioning
confidence: 99%